2014
DOI: 10.4269/ajtmh.13-0498
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses to O-Specific Polysaccharide and Lipopolysaccharide of Vibrio cholerae O1 Ogawa in Adult Bangladeshi Recipients of an Oral Killed Cholera Vaccine and Comparison to Responses in Patients with Cholera

Abstract: Abstract. Protective immunity to cholera is serogroup specific, and serogrouping is defined by the O-specific polysaccharide (OSP) of lipopolysaccharide (LPS). We characterized OSP-specific immune responses in adult recipients of an oral killed cholera vaccine (OCV WC-rBS) and compared these with responses in patients with cholera caused by Vibrio cholerae O1 Ogawa. Although vaccinees developed plasma immunoglobulin G (IgG), IgM, IgA antibody and antibody secreting cell (ASC, marker of mucosal response) to Oga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 49 publications
(107 reference statements)
3
47
2
Order By: Relevance
“…We have also found that OSP serum responses are much more prominent following naturally acquired disease than following vaccination with oral killed cholera vaccine, especially in young children (30,31). This may in part be due to the fact that OSP is a polysaccharide and as such is a T cell-independent antigen.…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…We have also found that OSP serum responses are much more prominent following naturally acquired disease than following vaccination with oral killed cholera vaccine, especially in young children (30,31). This may in part be due to the fact that OSP is a polysaccharide and as such is a T cell-independent antigen.…”
mentioning
confidence: 66%
“…Unfortunately, protection afforded by oral killed cholera vaccines is of lower magnitude and of shorter duration in children under 5 years of age than that in older children and adults and than that afforded by naturally acquired disease in children 5 years of age and younger (22,23,31,43). We have also previously shown that vaccination with an oral killed cholera vaccine (Dukoral; whole-cell oral cholera vaccine supplemented with 1 mg/dose of recombinant nontoxic cholera toxin B subunit [CtxB]; WCrBS; Crucell, Sweden) in the youngest children is associated with a proregulatory (interleukin-10 [IL-10]) response, versus a proinflammatory (IL-17, interferon gamma, and IL-13) response seen in young children with naturally acquired cholera (47), and that OSP-specific memory B cell responses following oral killed cholera vaccination of adults are markedly blunted following vaccination compared to what occurs following naturally acquired disease (30). Whether OSP-specific How memory B cell responses targeting OSP, a T cell-independent antigen, develop in young children following naturally acquired cholera is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We quantified LPS- (prepared in house) [16] and cholera toxin B subunit- (CTB, gifts of A. M Svennerholm, Göteborg University) specific IgA, IgG and IgM antibody responses in plasma using a previously described kinetic enzyme-linked immunosorbent assay (ELISA) [14,17,18,19]. …”
Section: Methodsmentioning
confidence: 99%